Formulated compost: A new technique of organic matter recycling and enrichment of soil to boost crop yield - Saraswat, P K; Kumar, Sanjay; Tiwari, R C; Singh, V K (Indian Farming, 2015)
Modern agricultural practices have been exhausting the nutrientsupplying capacity of soil on one hand and the disposal of hugeamounts of various biodegradable organic wastes due to modernization posing a major threat to environmental ecosystem on other hand. Among the alternatives available, disposal into soil through recycling is more fruitful rather than other options as the soils have high metabolic rates.